MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS 5 DENGAN MENGGUNAKAN PEMBELAJARAN KONTEKSTUAL - RUBIYATI RUBIYATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research was carried out because of the low mathematics learning outcomes of grade 5 students at SD Negeri 1 Bategede for the 2022/2023 academic year. This is proven by the average value of daily test classes only reaching 66.05. While the minimum completeness criterion is 70.00. After the researchers conducted research through interviews and observations, the low mathematics learning outcomes were caused by many factors, including because teachers still used conventional learning methods, there were also many students who were not fluent in reading. So there are still many students who do not understand the material presented by the teacher. Of the two problems above, the researcher chose to change the way of learning, namely according to the title above